2018
DOI: 10.1038/s41419-017-0126-0
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 potentiates BMP-2-induced osteogenesis and adipogenesis via two different BMPR1A-mediated pathways

Abstract: Recombinant human bone morphogenetic protein-2 (rhBMP-2) is widely used in the clinic for bone defect reconstruction because of its powerful osteoinductive capacity. However, commercially available rhBMP-2 requires a high concentration in the clinical setting for consistent bone formation. A high dose of rhBMP-2 induces a promising bone formation yield but also leads to inflammation-related events, deteriorated bone quality, and fatty tissue formation. We hypothesize that the seemingly contradictory phenomenon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 43 publications
(62 reference statements)
3
45
0
Order By: Relevance
“…Another finding of this study is that the expression of the SASP protein, IL‐6, which is also a pro‐inflammatory cytokine, was markedly upregulated in IGFBP7‐treated fibroblasts. Importantly, IL‐6 and its receptor, IL‐6R, are elevated in bone‐derived mesenchymal stem cells, and IL‐6 signaling activates STAT3 phosphorylation and downstream signaling to induce osteogenic gene expression . Our study showed that neutralization of secreted IL‐6 abrogated fibroblast to osteoblast reprogramming, suggesting a key role of autocrine IL‐6 signaling in IGFBP‐mediated osteoblastic reprogramming.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Another finding of this study is that the expression of the SASP protein, IL‐6, which is also a pro‐inflammatory cytokine, was markedly upregulated in IGFBP7‐treated fibroblasts. Importantly, IL‐6 and its receptor, IL‐6R, are elevated in bone‐derived mesenchymal stem cells, and IL‐6 signaling activates STAT3 phosphorylation and downstream signaling to induce osteogenic gene expression . Our study showed that neutralization of secreted IL‐6 abrogated fibroblast to osteoblast reprogramming, suggesting a key role of autocrine IL‐6 signaling in IGFBP‐mediated osteoblastic reprogramming.…”
Section: Discussionmentioning
confidence: 62%
“…Importantly, IL-6 and its receptor, IL-6R, are elevated in bone-derived mesenchymal stem cells, and IL-6 signaling activates STAT3 phosphorylation and downstream signaling to induce osteogenic gene expression. 54,55 Our study showed that neutralization of secreted IL-6 abrogated fibroblast to osteoblast reprogramming, suggesting a key role of autocrine IL-6 signaling in IGFBP-mediated osteoblastic reprogramming. However, other mechanisms might also be worthy of investigation.…”
Section: Discussionmentioning
confidence: 74%
“…The BMP pathway is involved in numerous physiological and pathological processes [77]. BMPs control MSC regulation, such as lineage specification of adipocytes which are one of the major elements of the mammary gland microenvironment [78][79][80]. Alterations in BMP signaling have been implicated in metabolic disorders such as obesity in women [81,82].…”
Section: Bmp and Mammary Epithelial Stem Cellsmentioning
confidence: 99%
“…Then, when the cultured cell fusion degree reached between 60% and 70%, the cells were carefully sucked out in order the complete the culture medium, and 2 ml of osteogenic differentiation culture medium were added. The induced differentiation was stained on the 21st day [19,20] .…”
Section: Msc Differentiationsmentioning
confidence: 99%
“…During the maintenance of Solution B, fresh Solution B was used every three days. Then, the specimens were stained using oil red O [20,21] .…”
Section: Msc Differentiationsmentioning
confidence: 99%